Regulation of the cecal microbiota community and the fatty liver deposition by the addition of brewers’ spent grain to feed of Landes geese - Xu, Ping; Hong, Yuxuan; Chen, Pinpin; Wang, Xu; Li, Shijie; Wang, Jie; Meng, Fancong; Zhou, Zutao; Shi, Deshi; Li, Zili; Cao, Shengbo; Xiao, Yuncai (Frontiers in Microbiology, 2022)
The effects of brewers' spent grain (BSG) diets on the fatty liver deposition and the cecal microbial community were investigated in a total of 320 healthy 5-day-old Landes geese. These geese were randomly and evenly divided into 4 groups each containing 8 replicates and 10 geese per replicate. These four groups of geese were fed from the rearing stage (day 5 to 60) to the overfeeding stage (day 61 to 90). The Landes geese in group C (control) were fed with basal diet (day 5 to 90); group B fed first with basal diet in the rearing stage and then basal diet + 4% BSG in the overfeeding stage; group F first with basal diet + 4% BSG during the rearing stage and then basal diet in the overfeeding stage; and group W with basal diet + 4% BSG (day 5 to 90). The results showed that during the rearing stage, the body weight (BW) and the average daily gain (ADG) of Landes geese were significantly increased in groups F and W, while during the overfeeding stage, the liver weights of groups W and B were significantly higher than that of group C. The taxonomic structure of the intestinal microbiota revealed that during the overfeeding period, the relative abundance of Bacteroides in group W was increased compared to group C, while the relative abundances of Escherichia-Shigella and prevotellaceae_Ga6A1_group were decreased. Results of the transcriptomics analysis showed that addition of BSG to Landes geese diets altered the expression of genes involved in PI3K-Akt signaling pathway and sphingolipid metabolism in the liver. Our study provided novel experimental evidence based on the cecal microbiota to support the application of BSG in the regulation of fatty liver deposition by modulating the gut microbiota in Landes geese.